166 GLYCOSYLATED C-REACTIVE PROTEIN STIMULATES PROINFLAMMATORY MEDIATOR EXPRESSION IN RAT AORTIC SMOOTH MUSCLE CELLS. (1st January 2006) - Feng, W.; Xing, D.; Oparil, S.; Chen, Y. F.; Szalai, A. J.
Abstract : Background: It has been reported that human C-reactive protein (CRP) can be glycosylated in different pathological conditions (eg, lupus, leukemia, tuberculosis) and thereby exhibit variable binding characteristics. This study tested the hypothesis that nonglycosylated CRP (non-g-CRP) and glycosylated CRP (g-CRP) differ in their ability to induce proinflammatory mediator expression by rat aortic smooth muscle cells (RASMCs). Methods: Quiescent RASMCs were treated for 6 hrs with non-g-CRP versus g-CRP (0.5 to 5 μg/mL) separately purified to apparent homogeneity from 6 different patients, and then harvested for RNA extraction. Real time RT-PCR was performed to assess mRNA expression of chemokines (cytokine-induced neutrophil chemoattractant [CINC]-2 and monocyte chemoattractant protein [MCP]-1), interleukin (IL)-6 and adhesion molecules (intercellular adhesion molecule [ICAM]-1 and vascular cell adhesion molecule [VCAM]-1). Data (mRNA to 18S RNA ratios) were normalized to the mean mRNA levels of vehicle-treated RASMCs. Results: g-CRP dose dependently stimulated expression of CINC-2, MCP-1, IL-6, ICAM-1, and VCAM-1 in RASMCs (Table). Surprisingly, non-g-CRP had no effect on expression of the same proinflammatory mediators. Conclusion: g-CRP elicits more robust proinflammatory molecule mRNA production from RASMCs than non-g-CRP, in a pattern consistent with modulation of the vascular injury response. This finding may help further define the clinical utility of CRP in the context of heart and blood vessel disease.